Pengaruh Rasio Laba atas Investasi, Rasio Hutang atas Ekuitas, Rasio Kredit atas Dana Pihak Ketiga, dan Rasio Kredit Macet terhadap Rasio Kecukupan Modal - Roymon Panjaitan (Jurnal Ilmiah Aset, 2018)
Research on the selection of variable Capital Adequacy Ratio (CAR) as the dependent variables because the CAR is the most important indicator accordingto Bank Indonesia in keeping the health level of the bank. CAR is affect by many factors such as Return On Investment ( ROI ), Debt to Equity Ratio ( DER ), Loan to Deposit Ratio ( LDR ) and Non Performing Loan ( NPL). The population in this research is the retired Nationals Savings Bank, Tbk (financial report 2010 – 2015 ). Research samples taken by using purposive sampling technique. The research method used was explanatory by using multiple linear regression test. The results showed that there is a positive influence of Return On Investment ( ROI) , Loan to Deposit Ratio ( LDR ), and Non Performing Loan ( NPL) against Capital Adequacy Ratio ( CAR ), while there was a negative influence of Debt to Equity Ratio ( DER ) to the Capital Adequacy Ratio (CAR ).